A Case of Severe Spontaneous Pneumomediastinum in Acquired Immunosuppressed Child with Respiratory Syncytial Virus and Human Bocavirus Co-infection - (:unkn) unknown (My University, 2021)
Spontaneous pneumomediastinum is an uncommon, benign, and self-limiting disease based on the presence of free air in the mediastinal cavity. It can occur after a forced Valsalva’s maneuver due to a cough, emesis or during an asthma exacerbation. We present a 4-month-old girl infant with an autoimmune hemolytic anemia and lymphopenia, who was admitted to the pediatric intensive care unit due to respiratory distress. A suspected pneumomediastinum image on chest X-ray was documented by the chest tomography. A polymerase chain reaction of the nasopharyngeal secretions was positive for a respiratory syncytial virus and human bocavirus. Additionally, she was examined for an immune deficiency due to her lymphopenia. The patient required mechanical ventilatory support for 26 days. She was treated with antibiotics, antiviral, and antifungal agents and corticosteroids. Intravenous immunoglobulin, trimethoprim sulfamethoxazole, and fluconazole prophylaxis were continued because of the ongoing lymphopenia. At the end of five weeks, the patient was discharged with a normal lymphocyte count and without any respiratory distress. In immunosuppressed patients, respiratory diseases may be severe and long. Therefore, complications including pneumomediastinum can be seen more frequently in this group of patients.

Spontan pnömomediastinum, mediastinal kavitede serbest hava varlığına dayanan, nadir görülen, iyi huylu ve kendi kendini sınırlayan bir hastalıktır. Öksürük, kusma veya astım alevlenmesi nedeniyle yapılan zorunlu bir Valsalva manevrasından sonra ortaya çıkabilir. Bu olgu sunumunda, solunum sıkıntısı nedeniyle pediyatrik yoğun bakım ünitesine yatırılan, otoimmün hemolitik anemi ve lenfopenisi olan 4 aylık bir kız çocuğunu sunduk. Akciğer grafisindeki şüpheli pnömomediastinum görüntüsü akciğer tomografisi ile belgelendi. Nazofarengeal salgıların polimeraz zincir reaksiyonu, solunum sinsityal virüsü ve insan bokavirüsü için pozitifti. Hasta ek olarak lenfopeni nedeniyle bağışıklık yetersizliği açısından da tetkik edildi. Hasta 26 gün mekanik ventilatör desteğine ihtiyaç duydu. Bu sırada antibiyotik, antiviral ve antifungal ajanlarla ve kortikosteroidlerle tedavi edildi. Devam eden lenfopeni nedeniyle intravenöz immünoglobulin, trimetoprim sulfametoksazol ve flukonazol profilaksisi kullanıldı. Bağışıklık sistemi baskılanmış hastalarda, solunum yolu hastalıkları şiddetli ve uzun sürebilir. Ayrıca, pnömomediastinum gibi komplikasyonlar bu hasta grubunda daha sık görüldüğünden dikkatli olmakta fayda vardır.
Solunum Sinsityal Virüs ve İnsan Bokavirüs Ko-enfeksiyonu Olan Edinilmiş İmmün Yetmezlikli Çocuk Olguda Ciddi Bir Spontan Pnömomediastinum Olgusu